2009
DOI: 10.3855/jidc.488
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of extended-spectrum beta-lactamase-producing Klebsiella pneumoniae in a tertiary care hospital in Tehran, Iran

Abstract: Background: Extended-spectrum beta (β)-lactamase (ESBL)-producing enterobacteria are major emerging pathogens in nosocomial infections. Methodology: The combination disk synergy test was used to evaluate 202 consecutive non-repeated Klebsiella pneumoniae (K. pneumonia) strains for ESBL production. The strains were isolated from various clinical specimens of hospitalized patients over the period from July 2005 to March 2007. Their antibiotic susceptibility pattern was also determined by the disk diffusion metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
27
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 15 publications
9
27
3
Order By: Relevance
“…Similar findings have been reported in other studies in Iran and Tanzania [9,10]. In these two studies imipenem was shown to be the most active antibiotic against the ESBL producing isolates and nitrofurantoin showed moderate activity.…”
Section: Discussionsupporting
confidence: 90%
“…Similar findings have been reported in other studies in Iran and Tanzania [9,10]. In these two studies imipenem was shown to be the most active antibiotic against the ESBL producing isolates and nitrofurantoin showed moderate activity.…”
Section: Discussionsupporting
confidence: 90%
“…In the present study, high resistance of K. pneumonia to numerous antibiotics was observed (Table 1). These results are similar to the reported results from Colombia and Iran (25,27), showing more than 97% resistance to ampicillin in K. pneumonia isolates. The situation indicates a threat to the community and a possibility that the K. pneumonia could have become resistance to many more antibiotics to which it showed susceptibility earlier.…”
Section: Discussionsupporting
confidence: 82%
“…The occurrence of ESBL among clinical isolates varies greatly in different geographic parts of Iran and is rapidly changing over time. A study in 2010 shows a prevalence of 32% in Kashan (24), 77% in Tehran (25), and 19.02% in Sanandaj (26). In the present study, high resistance of K. pneumonia to numerous antibiotics was observed (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of E. coli isolates that was found to be resistant to ciprofloxacin in our study (89.7%) was lesser than that reported by [25] in Egypt -in which 40% of the tested E. coli isolates in their study was found to be resistant to ciprofloxacin. Members of the Enterobacteriaceae family including E. coli often contain resistance determinants for other classes of antibiotics such as This article is available in: http://www.imedpub.com/applied-microbiology-and-biochemistry ISSN 2576-1412 the aminoglycosides, sulfonamides, and fluoroquinolones which are readily transmissible from one strain of organism to another and between different species of Gram-negative bacteria [26,27]. The E. coli strains in this study were found to be highly resistant to the cephalosporins and carbapenems used in this study especially cefoxitin (93.1%), ceftazidime (69.0%), cefotaxime (55.2%), imipenem (31.0%), meropenem (58.6%) and ertapenem (75.9%).…”
Section: Discussionmentioning
confidence: 99%